2(7s+3)-8s=2(3s+4)-12

Simple and best practice solution for 2(7s+3)-8s=2(3s+4)-12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(7s+3)-8s=2(3s+4)-12 equation:


Simplifying
2(7s + 3) + -8s = 2(3s + 4) + -12

Reorder the terms:
2(3 + 7s) + -8s = 2(3s + 4) + -12
(3 * 2 + 7s * 2) + -8s = 2(3s + 4) + -12
(6 + 14s) + -8s = 2(3s + 4) + -12

Combine like terms: 14s + -8s = 6s
6 + 6s = 2(3s + 4) + -12

Reorder the terms:
6 + 6s = 2(4 + 3s) + -12
6 + 6s = (4 * 2 + 3s * 2) + -12
6 + 6s = (8 + 6s) + -12

Reorder the terms:
6 + 6s = 8 + -12 + 6s

Combine like terms: 8 + -12 = -4
6 + 6s = -4 + 6s

Add '-6s' to each side of the equation.
6 + 6s + -6s = -4 + 6s + -6s

Combine like terms: 6s + -6s = 0
6 + 0 = -4 + 6s + -6s
6 = -4 + 6s + -6s

Combine like terms: 6s + -6s = 0
6 = -4 + 0
6 = -4

Solving
6 = -4

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 3x+13+25=2+7x | | 56-6=8 | | 3x-2/2x+1=-2 | | -9(2w-9)=0 | | K^2+5k+8=2 | | 50y=200 | | 18x-4x=9-3x | | 4(4-a)-2(a-4)=-10a-2a | | 4x-(30-x)+25=80 | | 15+4x+60=11x+12 | | 30+you=7 | | 2*(24/2y)*y=48 | | 5u(8u-1)=0 | | 4y=14-2x | | -1=-4+b | | (x^69-i^69)(x^69+i^69)=0 | | dy/dx=1/(2x-y^2) | | 7(x+2)=2x+57 | | 108=4z | | y=1/(2x-y^2) | | 0.5=1-e^-((t-1)/10) | | 4(4-a)-2(a-4)=-10-2a | | -2(5v-3)+3v=3(v+4) | | 7x+19+2x+15=133 | | -4h+6=-6h-8 | | 21b=14+b | | -17=m+71 | | 126=3p | | 1/3r-5=6 | | X*(x-5)=126 | | a+3b+5c=30000 | | 5r(r-7)=0 |

Equations solver categories